Determinants of Intention and Attempt to Quit Smoking: A Study in Kalidawir Tulungagung - Yuliawati, Riza; Yuliawati, M. Ali; Indasah, Indasah (P3M Politeknik Negeri Jember, 2023)
Smoking cessation has been widely known as the right step to improve health. However, it has a low success rate. This research aims to identify demographic attributes (age, sex, income, and education), tobacco knowledge and spending and their impacts on smoking cessation intention and attempts in Kalidawir, Tulungagung Districts. A survey of 111 adult smokers is conducted using the GATS questionnaire. The data is analyzed using binary logistic regression. Most respondents, as many as 70 (63.1%), expressed a desire to quit smoking. Meanwhile, 41 respondents (36.9%) had no intention to quit smoking. Unfortunately, less than half, which is 43 (38.7%), had ever tried to quit smoking and more than half of the respondents, as many as 68 (61.3%), stated that they had never tried to quit smoking. Level of education and tobacco spending has a significant impact on intention to quit smoking (p-value 0,018 and p-value 0,024). While age, income, sex and knowledge do not affect the intention to quit smoking (p-value 0,954; p-value 0,145; p-value 0,975; and p-value 0,639). Education income and tobacco spending significantly impact the attempt to quit smoking (p-value 0,001; p-value 0,001 and p-value 0,008). While age, sex and knowledge do not affect the attempt to quit smoking (p-value 0,359; p-value 0,477; and p-value 0,993). Level of education and tobacco spending have significant impacts on intention and attempt to quit smoking while income only has an impact on smoking cessation attempts. The tobacco control program should consider these factors and make more comprehensive interventions.